THE MIDDLE RIPHEAN TIME ON THE WESTERN SLOPE OF THE SOUTHERN URALS: MINERAGENIC AND GEODYNAMIC IMPLICATIONS - Krupenin M.T. (My University, 2004)
The Bashkir Meganticlinorium (BM) is on the western slope of the southern Urals. The Lower and Middle Riphean sedimentary sequences of the BM host very large stratiform magnesite and siderite deposits, barite, lead, and zinc deposits and occurrences, and vein-type fluorite deposits. New geological and geochronological data that specify formation conditions and the age of the stratiform ore mineralization in this region show that generation of ore-bearing fluids in the Middle Riphean sedimentary basin in the eastern part of the East European Platform was related to the reactivation of rifting 1230-1010 Ma ago, i.e., during the time that approximately coincides with and serves as a specific reflection of the Grenville orogenic cycle.
Keywords: Riphean; Precambrian::Proterozoic::Riphean; Докембрий::Протерозой::Рифей